Axial performance of RC columns with glass-fiber grids as peripheral hoops. Issue 1 (2nd January 2020) - Hwang, Y. H.; Yang, K. H.; Choi, Y. S.
ABSTRACT: The present study aimed to investigate the significance and limitation for the practical application of high-flexibility glass-fiber (GF) grids as an alternative of conventional steel hoops in reinforced concrete (RC) columns. The application of GF grids was also tested for the jacket section to retrofit the deficient columns of which configuration is impractical due to the interference of the existing column. Five virgin columns and two RC jacketed columns were tested under concentric axial loads. Main test parameters were the arrangement type and amount of wrapped GF grids with the combination of conventional steel hoops. The effectiveness of GF grids on confining concrete was examined through the assessment of axial ductility ratios of columns and stress–strain curves of confined concrete. All columns exhibited the tensile fracture of GF grids immediately after the peak strength of columns, which accelerated the crushing of core concrete and buckling of longitudinal reinforcement. Thus, the axial ductility ratios measured in the present columns with GF grids were commonly lower than those of the tied columns with conventional steel hoops at the same transverse reinforcement index. Overall, a more elaborate treatment is required for improving the tensile strength and elongation capacity of GF grids to apply for an alternative of steel hoops in tied columns.